2013
DOI: 10.1142/s2010135x13500045
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pyroelectric properties of PZT/PVDF-TrFE composites using calcined PZT ceramic powders

Abstract: The effects of calcined lead–zirconate–titanate (PZT) powders on the electric properties of PZT/polyvinylidene-trifluorethylene copolymer (PVDF-TrFE) composites thick films were studied in this paper. Firstly, the PZT powders synthesized by hydrothermal method were calcined at different temperatures ranging from 300°C to 900°C, and then the PZT/PVDF-TrFE composites films were produced by casting PZT/PVDF-TrFE suspension onto the indium-tin-oxide (ITO)-coated glass substrates. Electric properties, including die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The surface of ceramics can be activated by calcination. 118,131,139,140 Wu et al 141 studied the dielectric properties of 0-3 PZT/P(VDF-co-TrFE) composite after calcination of the PZT fillers at different temperatures. TEM images showed less aggregation and the presence of fewer cavities between the ceramic fillers and the fluorinated matrix for calcinated PZT.…”
Section: Physical Modifications Of the Fillersmentioning
confidence: 99%
“…The surface of ceramics can be activated by calcination. 118,131,139,140 Wu et al 141 studied the dielectric properties of 0-3 PZT/P(VDF-co-TrFE) composite after calcination of the PZT fillers at different temperatures. TEM images showed less aggregation and the presence of fewer cavities between the ceramic fillers and the fluorinated matrix for calcinated PZT.…”
Section: Physical Modifications Of the Fillersmentioning
confidence: 99%
“…Based on this approach, researchers have found that the dielectric properties of composites can be greatly enhanced by heat-treated ceramics doping [20]. For instance, calcined lead zirconate titanate (PZT) ceramics doping can improve the dielectric properties of composites [21]. Moreover, according to the research results from Schumacher et al [22], the permittivity of composites can be significantly improved through heat-treated barium titanate (BT) and poly (vinyl acetate-phenylethyl) dilute doping, which is 2.7 times larger than composites doping with BT without heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…From the synthesis results, the crystal structures were identified using the X-Ray Diffractometer (XRD) and analyzed using the Highscore program. The results of optimizing several polling parameters were applied to PZT piezoelectric composite materials with Polyvinylidene Fluoride (PVDF), as developed by Chuan Gui Wu [10]. The high voltage used in this study empowers Flyback TV.…”
Section: Introductionmentioning
confidence: 99%